Enhancing Student Creativity in Poster Design Learning Through Deep Learning Approach - Romi, Romi; Tangsi, Tangsi; Sukarman B, Sukarman B (Journal of Innovation and Research in Primary Education, 2025)
This classroom action research investigated the implementation of the deep learning approach to enhance student creativity in poster design learning among grade XI students at SMA Negeri 21 Gowa, Indonesia. The study addressed the persistent problem of low creativity levels resulting from conventional, product-oriented instruction that inadequately supported creative exploration and reflective thinking. Employing Kemmis and McTaggart's action research model, the study involved 36 students over three cycles (pre-cycle, Cycle I, and Cycle II) with data collected through observation, performance assessments, interviews, and documentation. Student creativity was evaluated across three indicators: idea fluency, design technique application, and visual message communication. The implementation systematically integrated meaningful learning, mindful learning, and joyful learning principles through thematic project-based activities, reflective dialogues, and personalized feedback. Results demonstrated significant progressive improvement in mean creativity scores from 58% (moderately creative) in the pre-cycle to 76% (creative) in Cycle I, and 85% (highly creative) in Cycle II, with 75% of students achieving highly creative status by the final cycle. The findings validate that deep learning approaches effectively transform visual arts education from mechanical, outcome-focused instruction to process-oriented pedagogy that cultivates authentic creativity, critical thinking, and reflective capacities aligned with 21st-century educational demands.